Li7La3Zr2O12 Garnet Solid Polymer Electrolyte for Highly Stable All-Solid-State Batteries - Nguyen, Quoc Hung; Luu, Van Tung; Nguyen, Hoang Long; Lee, Young-Woo; Cho, Younghyun; Kim, Se Young; Jun, Yun-Seok; Ahn, Wook (Frontiers in Chemistry, 2021)
All-solid-state batteries have gained significant attention as promising candidates to replace liquid electrolytes in lithium-ion batteries for high safety, energy storage performance, and stability under elevated temperature conditions. However, the low ionic conductivity and unsuitability of lithium metal in solid polymer electrolytes is a critical problem. To resolve this, we used a cubic garnet oxide electrolyte (Li7La3Zr2O12 – LLZO) and ionic liquid in combination with a polymer electrolyte to produce a composite electrolyte membrane. By applying a solid polymer electrolyte on symmetric stainless steel, the composite electrolyte membrane shows high ionic conductivity at elevated temperatures. The effect of LLZO in suppressing lithium dendrite growth within the composite electrolyte was confirmed through symmetric lithium stripping/plating tests under various current densities showing small polarization voltages. The full cell with lithium iron phosphate as the cathode active material achieved a highest specific capacity of 137.4 mAh g−1 and a high capacity retention of 98.47% after 100 cycles at a current density of 50 mA g−1 and a temperature of 60°C. Moreover, the specific discharge capacities were 137 and 100.8 mAh g−1 at current densities of 100 and 200 mA g−1, respectively. This research highlights the capability of solid polymer electrolytes to suppress the evolution of lithium dendrites and enhance the performance of all-solid-state batteries.